2019
DOI: 10.1088/1757-899x/523/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the using waste tire rubber and natural ziolite as Asphalt and Cement replacements to compressive strength of Semi-Flexible Pavement

Abstract: The objective of this research is to study the compressive strength of semi-flexible pavement by using waste tire rubber and natural zeolite as asphalt and cement replacements. The mix design of porous asphalt is started with a determination of optimum asphalt proportion with open-graded aggregate as specified in Australian Asphalt Pavement Association (AAPA) 2004. The asphalt was then replaced by 3 %, 4 % and 5 % of waste tire rubber and the Marshall test were conducted. The cement mortar with 0 %, 5 %, 10 %,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…La prueba de resistencia a la compresión se realizó con base en ASTM D1074-02 a la edad de 14 días. Los resultados de la prueba mostraron que la mayor resistencia a la compresión se alcanza con el 5% CR, que es de 15,43 MPa (Hamzani, Munirwansyah, Hasan y Sugiarto, 2019). Si bien es cierto la norma ASTM D1074-02 no menciona el tiempo en el que se debe de ejecutar el ensayo los autores Hamzani, Munirwansyah, Hasan y Sugiarto, tomaron el criterio de realizar la prueba a los 14 días.…”
Section: Desarrollo Y Discusiónunclassified
“…La prueba de resistencia a la compresión se realizó con base en ASTM D1074-02 a la edad de 14 días. Los resultados de la prueba mostraron que la mayor resistencia a la compresión se alcanza con el 5% CR, que es de 15,43 MPa (Hamzani, Munirwansyah, Hasan y Sugiarto, 2019). Si bien es cierto la norma ASTM D1074-02 no menciona el tiempo en el que se debe de ejecutar el ensayo los autores Hamzani, Munirwansyah, Hasan y Sugiarto, tomaron el criterio de realizar la prueba a los 14 días.…”
Section: Desarrollo Y Discusiónunclassified
“…Te compressive strength test was carried out on the above, and the test results showed that when the natural zeolite content was 15% and the waste tire rubber content was 5%, the compressive strength reached 15.43 MPa. In addition, Hamzani et al [21] also used materials including waste tire rubber (WTR) and natural zeolite to improve the deformation and fatigue failure of semifexible pavement (SFP) under cyclic loading. Tey carried out a simple support beam with a span length of 30 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural pozzolan such as zeolite and diatomite has also intensively studied [5][6][7][8][9][10][11]. Incorporating of waste tire rubber (WTR) as an additive and natural zeolite as cement replacement in semi flexible pavement has shown to increase those parameters [12,13].…”
Section: Introductionmentioning
confidence: 99%